The effects of impulsivity and proactive inhibition on reactive inhibition and the go process: insights from vocal and manual stop signal tasks - Castro-Meneses, Leidy J.; Johnson, Blake W.; Sowman, Paul F. (Frontiers in Human Neuroscience, 2015)
This study measured proactive and reactive response inhibition and their relationships with self-reported impulsivity. We examined the domains of both vocal and manual responding using a stop signal task (SST) with two stop probabilities: high and low probability stop (1/3 and 1/6 stops respectively). Our aim was to evaluate the effect stop probability would have on reactive and proactive inhibition. We tested 44 subjects and found that for the high compared to low probability stop signal condition, more proactive inhibition was evident and this was correlated with a reduction in the stop signal reaction time (SSRT). We found that reactive inhibition had a positive relationship with dysfunctional but not functional impulsivity in both vocal and manual domains of responding. These findings support the hypothesis that proactive inhibition may pre-activate the network for reactive inhibition.